National surveillance of cancer survival in Iran (IRANCANSURV): Analysis of data of 15 cancer sites from nine population‐based cancer registries. Issue 12 (6th August 2022) - Nemati, Saeed; Saeedi, Elnaz; Lotfi, Fereshte; Nahvijou, Azin; Mohebbi, Elham; Ravankhah, Zahra; Rezaeianzadeh, Abbas; Yaghoobi‐Ashrafi, Majid; Pirnejad, Habbiballah; Golpazir, Arash; Dolatkhah, Roya; Alvand, Saba; et al.
Abstract: Cancer survival is a key indicator for the national cancer control programs. However, survival data in the East Mediterranean region (EMR) are limited. We designed a national cancer survival study based on population‐based cancer registries (PBCRs) from nine provinces in Iran. The current study reports 5‐year net survival of 15 cancers in Iranian adults (15‐99 years) during 2014 to 2015 in nine provinces of Iran. We used data linkages between the cancer registries and the causes of death registry and vital statistics and active follow‐up approaches to ascertain the vital status of the patients. Five‐year net survival was estimated through the relative survival analysis. We applied the international cancer survival standard weights for age standardization. Five‐year survival was highest for prostate cancer (74.9%, 95% CI 73.0, 76.8), followed by breast (74.4%, 95% CI 72.50, 76.3), bladder (70.4%, 95% CI 69.0, 71.8) and cervix (65.2%, 95% CI 60.5, 69.6). Survival was below 25% for cancers of the pancreas, lung, liver, stomach and esophagus. Iranian cancer patients experience a relatively poor prognosis as compared to those in high‐income countries. Implementation of early detection programs and improving the quality of care are required to improve the cancer survival among Iranian patients. Further studies are needed to monitor the outcomes of cancer patients in Iran and other EMR countries. Abstract : What's new? The ultimate goal of a national cancer program is increased survival, and survival data is critical for evaluating how well a program is doing. Here, the authors conducted a national cancer survival study based on population‐based cancer registries from 15 sites in Iran covering about 50 million people. They found that survival among Iranian patients tends to be lower compared to patients in higher‐income countries, suggesting a need for better early‐detection programs and increased access to high quality care. This study is one of the first comprehensive attempts to examine population‐based cancer survival in the Eastern Mediterranean region.